2014
DOI: 10.14301/llcs.v5i2.276
|View full text |Cite
|
Sign up to set email alerts
|

Holistic housing pathways for Australian families through the childbearing years

Abstract: For the previous generation, the typical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Finally, research should focus more on the dynamic nature of individuals' lives and exploit various novel methods to measure this. Examples could be the application of the techniques of (multichannel) sequence analysis (Spallek, Haynes, and Jones 2014) or multistate models (Kulu and Steele 2013), allowing the simultaneous study of a number of life events and paths with and without adjusting patterns for the various socioeconomic and cultural characteristics of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research should focus more on the dynamic nature of individuals' lives and exploit various novel methods to measure this. Examples could be the application of the techniques of (multichannel) sequence analysis (Spallek, Haynes, and Jones 2014) or multistate models (Kulu and Steele 2013), allowing the simultaneous study of a number of life events and paths with and without adjusting patterns for the various socioeconomic and cultural characteristics of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is simple if the number of possible combinations is moderate, but the combined state space grows rapidly as the number of domains and/or states grows. Multichannel sequence analysis has been used for computing pairwise dissimilarities and finding clusters in complex sequence data (see, e.g., Eerola and Helske, 2016;Müller et al, 2012;Spallek et al, 2014). However, the dissimilarities are largely affected by the chosen dissimilarity metric and the cluster allocation may not be well suited to borderline cases.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship has been consistently identified in the literature, where the transition to home ownership has been found to be linked with events that take place early in the life course, in particular, with family formation and birth of the first and consecutive child (Feijten & Mulder, 2002;Kulu & Milewski, 2007;Mulder, 2006). Even though the order of the events can and has been explored in previous research (Spallek, Haynes, & Jones, 2014), investigating the causality of these events is nevertheless difficult. The question of whether fertility planning influences the decision to enter home ownership; or whether the transition to home ownership influences the decision to have a child, cannot be answered by simply knowing the order of event occurrence.…”
Section: Order and Causalitymentioning
confidence: 73%
“…The traditional Australian pathway was described as first having a child, followed by the transition to home ownership before having more children (Winter & Stone, 1999;Yates, 2007a). Recent research, however, reported a deviance from this clearly defined pathway to more diverse interactions of these events (Spallek et al, 2014). …”
Section: Research Questionsmentioning
confidence: 99%